Rancang Bangun Prototipe Aplikasi PAKARS Validation dalam Pengelolaan Piutang Mahasiswa Pascasarjana - Sinuraya, Amri (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
Delays in tuition payments by students pose a serious challenge to the financial stability of universities. This problem is often exacerbated by the suboptimal use of available flexible payment schemes due to the lack of information received by students and inefficient administrative processes. This study aims to design and build a prototype application called “Pakars Validation” as a technological solution for managing student receivables, particularly at the postgraduate level. This application is designed to mitigate credit risk by focusing on two main aspects: identifying student eligibility administratively and academically through a rule-based knowledge base, and increasing their financial awareness regarding payment obligations. By adopting the Research and Development method and the Waterfall System Development Life Cycle (SDLC) model, this prototype was developed with a client-server architecture. This system integrates academic and financial data to run an inference engine that automatically evaluates student status. In addition, an automated email communication system was implemented as a mediating variable to efficiently convey billing information, deadlines, and payment restructuring options. The result of this research is a functional prototype model that can be a tool for college management in conducting risk assessments in a more systematic, consistent, and accurate manner. The “Pakars Validation” design is expected to not only reduce the level of bad debt, but also provide practical contributions to educational institutions in designing more effective and data-driven financial communication strategies.